Integrating new memories into the hippocampal network activity space - Gava, GP; McHugh, SB; Lefevre, L; Lopes Dos Santos, V; Trouche, S; El-Gaby, M; Schultz, SR; Dupret, D (Nature Research, 2021)
By investigating the topology of neuronal co-activity, we found that mnemonic information spans multiple operational axes in the mouse hippocampus network. High-activity principal cells form the core of each memory along a first axis, segregating spatial contexts and novelty. Low-activity cells join co-activity motifs across behavioral events and enable their crosstalk along two other axes. This reveals an organizational principle for continuous integration and interaction of hippocampal memories.